2017
DOI: 10.1111/jch.12978
|View full text |Cite
|
Sign up to set email alerts
|

The concept of crosstalk‐directed embryological target mining and its application to essential hypertension treatment failures

Abstract: This review aims to introduce the novel concept of embryological target mining applied to interorgan crosstalk network genesis, and applies embryological target mining to multidrug-resistant essential hypertension (a prototype, complex, undertreated, multiorgan systemic syndrome) to uncover new treatment targets and critique why existing strategies fail. Briefly, interorgan crosstalk pathways represent the next frontier for target mining in molecular medicine. This is because stereotyped stepwise organogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Percutaneous catheter-based radiofrequency ablation of afferent and efferent sympathetic nerves of renal arteries is one such technique and is the most widely researched to date. It is purported to address certain interorgan crosstalk pathways that may be upregulated in non-atherosclerotic nephrogenic hypertension [ 9 ]. Due to the risk of contrast-induced nephropathy associated with the use of iodinated contrast materials, patients with an estimated glomerular filtration rate (eGFR) <45 mL/min/1.73 m 2 have been excluded from major trials of renal sympathetic denervation (RSDN).…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous catheter-based radiofrequency ablation of afferent and efferent sympathetic nerves of renal arteries is one such technique and is the most widely researched to date. It is purported to address certain interorgan crosstalk pathways that may be upregulated in non-atherosclerotic nephrogenic hypertension [ 9 ]. Due to the risk of contrast-induced nephropathy associated with the use of iodinated contrast materials, patients with an estimated glomerular filtration rate (eGFR) <45 mL/min/1.73 m 2 have been excluded from major trials of renal sympathetic denervation (RSDN).…”
Section: Introductionmentioning
confidence: 99%
“…These patients have more target organ damage compared with patients with hypertension who achieve target BPs with treatment. There is no accepted therapeutic norm for these patients, which has created a longstanding therapeutic dilemma . However, a new emerging technique was recently introduced: renal sympathetic denervation.…”
mentioning
confidence: 99%
“…There is no accepted therapeutic norm for these patients, which has created a longstanding therapeutic dilemma. 4,5 However, a new emerging technique was recently introduced: renal sympathetic denervation. In initial studies, renal sympathetic denervation was demonstrated to be effective in reducing BP in patients with resistant hypertension.…”
mentioning
confidence: 99%
“…Finally, the inclusion of only patients naïve to anti-RAAS medication is especially interesting from the perspective of purported cross-talk pathways underlying ARVH pathophysiology (e.g. the mechanism of RAAS activation as a mechanism of thiazide resistance) [ 4 , 5 ]. Since most atherosclerotic patients are not candidates for renal denervation (due to inability to provide catheter/true vessel wall contact deep to plaque), the future of intervention for ARVH (until endovascular regenerative techniques such as stem cell embolization come to fruition) will focus on angioplasty and stenting (with or without drug-eluting technology) in the near term [ 2 ].…”
mentioning
confidence: 99%